For a female pedagogy: a look at some North African Islamic feminists - Carla Roverselli (University of Bologna, 2020)
Intercultural education has several objectives: remove educational inequalities, promote social justice, encourage coexistence as subjects of equal dignity who must be given equal opportunities. This pedagogical approach looks carefully at all the differences: those cultural and gender ones. The article proposes to reflect on the thought of two North African Islamic women Nawal El Saadawi and Assia Djebar. Both are feminists and yet diverge in several respects. Assia is an Algerian writer and director. She writes in French, the language of the colonizers, because she does not accept Arabic as the official language in the land of Algeria, because it is the language that his father taught her, the language of freedom. Nawal is an Egyptian female doctor, psychiatrist. She writes in Arabic because she addresses an Arab audience: she wants to get his thoughts to women but also to men, those who manage power. The presentation of the thought of these two women is aimed at deepening the knowledge of a culture different from the western and Christian one. It also serves to highlight the contribution of Islamic women to women's emancipation.